2018
DOI: 10.1101/259523
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

De novo acetate production is coupled to central carbon metabolism in mammals

Abstract: In cases of nutritional excess, there is incomplete catabolism of a nutritional source and secretion of a waste product (overflow metabolism), such as the conversion of glucose to lactate (the Warburg Effect) in tumors. Here we report that excess glucose metabolism generates acetate, a key nutrient whose source has been unclear. Conversion of pyruvate, the product of glycolysis, to acetate occurs through two mechanisms: 1) coupling to reactive oxygen species (ROS), and 2) a neomorphic enzyme activity from keto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
(70 reference statements)
3
7
0
Order By: Relevance
“…Conversely, we did not detect enrichment of citrate, malate, or succinate in the nuclear fraction (Figure S2C). Nuclei can utilize 13 C-pyruvate for histone acetylation (Liu et al, 2018), and we observed robust histone acetylation in the nuclear fraction and not the cytosolic fraction, further confirming the purity of the nuclear preparations ( Figure S2C). As an internal control, the cytosolic fraction was also subjected to protease digestion to demonstrate the removal of proteins and enzyme activity after treatment (Figures 2H,S2B,and S2C).…”
Section: Glycogen Is Synthesized De Novo In Nucleisupporting
confidence: 73%
See 2 more Smart Citations
“…Conversely, we did not detect enrichment of citrate, malate, or succinate in the nuclear fraction (Figure S2C). Nuclei can utilize 13 C-pyruvate for histone acetylation (Liu et al, 2018), and we observed robust histone acetylation in the nuclear fraction and not the cytosolic fraction, further confirming the purity of the nuclear preparations ( Figure S2C). As an internal control, the cytosolic fraction was also subjected to protease digestion to demonstrate the removal of proteins and enzyme activity after treatment (Figures 2H,S2B,and S2C).…”
Section: Glycogen Is Synthesized De Novo In Nucleisupporting
confidence: 73%
“…Pyruvate supplies a significant portion of intracellular acetate required for histone acetylation (Liu et al, 2018). Malin-directed glycogenolysis could provide an additional source for the nuclear pyruvate pool.…”
Section: Nuclear Glycogen Is a Substrate Pool For Histone Acetylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Mpc depletion resulted in less intercellular citrate, cytosolic acetyl-CoA can be compensated by accumulated pyruvate. Further, pyruvate can be catalyzed into acetate, and in turn to acetyl-CoA in cytosol [27]. Indeed, we found that Mpc depletion blocks the entry of pyruvate into the mitochondria and leads to more pyruvate release.…”
Section: Histone Acetylation and Macrophage Activationmentioning
confidence: 65%
“…During increased energy demand or restricted TCA cycle function, all of the pyruvate-derived acetyl-CoA might have not successfully entered the TCA cycle and thus the excess can be hydrolyzed to acetate and released into the circulation (42,43). Acetate can be produced from pyruvate via enzymatic and non-enzymatic reactions including pyruvate dehydrogenase (PDH) and reactive oxygen species (ROS) (44), respectively, and PDH activity (45) and ROS levels ( 16) are increased by exercise and/or myotube contractions. In addition, hyperactive glucose metabolism and nutritional excess have been related to incomplete metabolism and excretion of metabolites, which lead to promoted conversion of pyruvate to acetate (44).…”
Section: Discussionmentioning
confidence: 99%